PENGARUH PBL BERBASIS ISU SOSIAL-SAINTIFIK TERHADAP LITERASI LINGKUNGAN DAN CRITICAL THINKING PADA MATERI EKOSISTEM SISWA KELAS X DI SMA NEGERI 13 MEDAN - Hermaliana, Nadia; Arwita, Widya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of environmental literacy and critical thinking skills of students in ecosystem learning is a problem that needs attention because students are expected not only to understand ecological concepts but also to analyze environmental problems and determine appropriate solutions. This study aimed to determine the effect of the Problem Based Learning (PBL) model based on Socio-Scientific Issues (SSI) on students’ environmental literacy and critical thinking skills in ecosystem topics. This research employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The research sample consisted of 60 Grade X students of SMA Negeri 13 Medan, with 30 students in the experimental class and 30 students in the control class. The experimental class was taught using PBL based on SSI, while the control class was taught using direct instruction. Data were collected through multiple-choice tests and questionnaires for environmental literacy and essay tests for critical thinking. Data were analyzed using the Shapiro-Wilk normality test, Levene homogeneity test, and Independent Samples t-test. The results showed that the experimental class obtained a higher post-test mean environmental literacy score of 82.92 than the control class of 71.97, with a significance value of 0.01. For critical thinking, the experimental class obtained a post-test mean of 54.29, compared with 45.93 in the control class, with a significance value of 0.02. Thus, PBL based on SSI had a significant effect on students’ environmental literacy and critical thinking skills in ecosystem learning.